Multiple Congenital Colonic Stenosis: A Rare Gastrointestinal Malformation - Zambaiti Elisa; Chiaramonte Cinzia; Salerno Sergio; Li Voti Giuseppe; Siracusa Fortunato (Hindawi Limited, 2016)
Congenital colonic stenosis is a rare pediatric condition. Since 1968, only 16 cases have been reported in the literature. To the authors' knowledge, multiple congenital colonic stenosis has not been previously reported in the literature. We report the case of a 2-month-old male, presented at our Neonatal Intensive Care Unit with a suspicion of intestinal malrotation. Clinical examination revealed persistent abdominal distension. During the enema examination, the contrast medium appeared to fill the lumen of the colon up to three stenotic segments and could not proceed further. Intraoperatively we confirmed the presence of four types of colonic atresia, located in the ascending, transverse, and descending colon, respectively, plus appendix atresia. First surgical steps consisted in resection of proximal stenotic segment, appendix removal, proximal cecostomy, and distal colostomy on ascending colon in order to preserve colonic length. Histopathological examination confirmed the diagnosis of colonic stenosis. Final surgical step consisted in multiple colocolostomy and enteroplasty. A planned two-stage procedure, consisting of resection with colostomy for decompression as the first step and a later anastomosis, is recommended in order to allow bowel length preservation.